Cross validation of bioelectrical impedance equations for men - Maria Fátima Glaner (Universidade Federal de Santa Catarina, 2005)
The purpose of this study was to analyze the cross validity of bioimpedance equations (BIA) on the estimation of the fat free mass (FFM) of 44 men, with mean age of 24.98 ± 3.40 years and relative body fat (%BF) of 17.15 ± 6.41%. A dual energy x-ray absorptiometry was used as a reference method for %BF and FFM. Total body resistance was assessed by the Biodynamics (Model 310). The equations analyzed in this study were: two equations (Eq.1 and 2) developed by Carvalho e Pires Neto (1998); one equation (Eq. 3) developed by Rising et al.(1991); one equation (Eq. 4) developed by Oppliger et al.(1991); two equations (Eq. 5 (%FM < 20%) and Eq. 6 (%FM ≥ 20%) developed by Segal et al. (1988). The validation criteria proposed by Lohman (1991) was used in this study. The correlations were high and significant oscillating from 0.906 (Eq. 2) to 0.981 (Eq. 6). The equations 1 to 5 significantly overestimated (p < 0.001) FFM and the mean differences ranged from 1.32 kg (Eq. 5) to 5,90 kg (Eq. 4). The equation 6 met all the validity criteria. The validity coefficient was r = 0.981 and the mean difference was -0.38 kg. The Segal et al.(1988) fatness specific equation (Eq. 6) for men (%FM ≥ 20%) was the only one that met the concurrent validity criteria. The equation 6 showed a non significant difference on FFM and the standard error of estimate was 0.90kg. RESUMO Este estudo teve como objetivo analisar a validade concorrente de equações de impedância bioelétrica (IB) para estimar a massa corporal livre de gordura (MLG), em 44 homens, com idade média de 24,98 ± 3,40 anos e gordura relativa (%G) de 17,15 ± 6,41 %. A absortometria de raio-x de dupla energia foi usada como critério, para mensurar a %G e a MLG, e para obter estas variáveis decorrentes das equações de IB foi utilizado o Biodynamics (Modelo 310). As equações de IB analisadas neste estudo foram: duas equações (Eq. 1 e 2) de Carvalho e Pires Neto (1998); uma equação (Eq. 3) de Rising et al. (1991); uma equação (Eq. 4) de Oppliger et al.(1991); duas equações (Eq. 5 (%G < 20%) e Eq. 6 (%G ≥ 20%) de Segal et al. (1988). Os critérios adotados para validação foram os propostos por Lohman (1991). Todas as correlações foram altas e significativas, oscilando de 0,906 (Eq. 2) a 0,981 (Eq. 6). As equações 1 a 5 superestimaram de forma significativa (p < 0,001) a MLG, sendo que os erros constantes variaram de 1,32 kg (Eq. 5) a 5,90 kg (Eq. 4). A equação 6 atendeu a todos os critérios de validação, apresentando: correlação = 0,981; erro constante = -0,38 kg; erro total = 1,10 kg. Esta equação de Segal et al.(1988), para homens com gordura relativa ≥ 20% (Eq. 6) foi a única que apresentou validade concorrente, estimando a MLG, com um erro padrão de estimativa 0,90 kg.